Answer:
Following are the answer to this question:
Explanation:
The principle vale of Arg(3)
![Arg(3)=-\pi+\tan^(-1) ((|Y|)/(|x|))](https://img.qammunity.org/2021/formulas/mathematics/college/v9ujbjq69zjr1j7ml1v4a4n7d50a9m8o9j.png)
The principle value of the
![\logi= \log(0+i)\ \ \ \ \ _(where) \ \ \ x=0 \ \ y=1> 0](https://img.qammunity.org/2021/formulas/mathematics/college/appz4e2xpgr85p5l77avgqvdzz43f0laap.png)
So, the principle value:
a)
![\to \log(i)=\log |i|+i Arg(i)\\\\](https://img.qammunity.org/2021/formulas/mathematics/college/zw2etdhvpohoqi7xib7t2e3ipsuy4ekq2p.png)
![=\log √(0+1)+i \tan^(-1)((1)/(0))\\\=\log 1 +i \tan^(-1)(\infty)\\\=0+i(\pi)/(2)\\\=i(\pi)/(2)](https://img.qammunity.org/2021/formulas/mathematics/college/elet0jksercqb9xmocaegtq8i0ybupfwmt.png)
b)
![\to \log(-i)= \log(0-i ) \ \ \ x=0 \ \ \ y= -1<0\\](https://img.qammunity.org/2021/formulas/mathematics/college/7ozbe397xj3mc6mpjgh44elmfqten6zk78.png)
Principle value:
![\to \log(-i)= \log|-i|+iArg(-i) \\\\](https://img.qammunity.org/2021/formulas/mathematics/college/x0inl6knthcd0tak1u34kkwu49zacpwnzr.png)
![=\log √(0+1)+i(-\pi+\tan^(-1)(\infty))\\\\=\log1 + i(-\pi+(\pi)/(2))\\\\=-i(\pi)/(2)](https://img.qammunity.org/2021/formulas/mathematics/college/mb9xd6xwfxn6ol0s8l1kr69hj9cqi2cfpg.png)
c)
![\to \log(-1+i) \ \ \ \ x=-1, _(and) y=1 \ \ \ x<0 and y>0](https://img.qammunity.org/2021/formulas/mathematics/college/4tkjorukindc2xhys7kls704bmrcp757g3.png)
The principle value:
![\to \log(-1+i)=\log |-1+i| + i Arg(-1+i)](https://img.qammunity.org/2021/formulas/mathematics/college/hobqq99tlggl5rxxuj93x49tvf96j6lzhu.png)
![=\log √(1+1)+i(\pi+\tan^(-1)((1)/(1)))\\\\=\log √(2) + i(\pi-\tan^(-1)(\pi)/(4))\\\\=\log √(2) + i\tan^(-1)(3\pi)/(4)\\\\](https://img.qammunity.org/2021/formulas/mathematics/college/29yxyl0h60pandcm1q4lvds2jrxr7w2o4e.png)
d)
![\to i^i=w\\\\w=e^(i\log i)](https://img.qammunity.org/2021/formulas/mathematics/college/cvijpv9s6ge5q1hf04nrxtpqnxy6n0i8he.png)
The principle value:
![\to \log i=i(\pi)/(2)\\\\\to w=e^{i(i (\pi)/(2))}\\\\=e^{-(\pi)/(2)}](https://img.qammunity.org/2021/formulas/mathematics/college/foyy08otupv6zamao1ca8zabx2zzdcrzxh.png)
e)
![\to (-i)^i\\\to w=(-i)^i\\\\w=e^(i \log (-i))](https://img.qammunity.org/2021/formulas/mathematics/college/ky7vvltsozu5axspmu3qw7aznqobg8y4pz.png)
In this we calculate the principle value from b:
so, the final value is
![e^{(\pi)/(2)}](https://img.qammunity.org/2021/formulas/mathematics/high-school/83svwkt2shbat27lexes27aiyzkw6i3z83.png)
f)
![\to -1^i\\\\\to w=e^(i log(-1))\\\\\ principle \ value: \\\\\to \log(-1)= \log |-1|+iArg(-i)](https://img.qammunity.org/2021/formulas/mathematics/college/40pv93jx1h755hv2gm2hcgle7tud115qxr.png)
![=\log √(1) + i(\pi-\tan^(-1)(0)/(-1))\\\\=\log √(1) + i(\pi-0)\\\\=\log √(1) + i\pi\\\\=0+i\pi\\=i\pi](https://img.qammunity.org/2021/formulas/mathematics/college/d672pfcolift3bzxtu43zbt54qdqo3yuyh.png)
and the principle value of w is =
![e^(\pi)](https://img.qammunity.org/2021/formulas/mathematics/college/56xxmwiouuyoo6turvgl6xn0mtxccvbkg7.png)
g)
![\to -1^(-i)\\\\\to w=e^(-i \log (-1))\\\\](https://img.qammunity.org/2021/formulas/mathematics/college/841n9qufum4t0ygpsjkkyjsvjgoxk3gcod.png)
from the point f the principle value is:
![\to \log(-1)= i\pi\\\to w= e^(-i(i\pi))\\\\\to w=e^(\pi)](https://img.qammunity.org/2021/formulas/mathematics/college/mktbicez8yjkaoq99h7ricpmtoyplb8yaf.png)
h)
![\to \log(-1-i)\\\\\ Here x=-1 ,<0 \ \ y=-1<0\\\\ \ principle \ value \ is:\\\\ \to \log(-1-i)=\log√(1+1)+i(-\pi+\tan^(-1)(1))](https://img.qammunity.org/2021/formulas/mathematics/college/1lh9quaea8jeyh9a6jyk1axfx9f3ptq6b9.png)
![=\log√(2)+i(-\pi+(\pi)/(4))\\\\=\log√(2)+i(-(3\pi)/(4))\\\\=\log√(2)-i(3\pi)/(4))\\](https://img.qammunity.org/2021/formulas/mathematics/college/1nhkyhccit6xfpg4xtl8i68ej14oirufx1.png)